2019
DOI: 10.1016/j.fertnstert.2019.07.1016
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged time to diagnosis of primary ovarian insufficiency (POI) in an urban reproductive endocrinology (RE) clinic

Abstract: Black women face unique intersectional challenges in their experience living with infertility. The results of this study may serve as a tool for improving physician-patient interactions and foster a better understanding of modern reproductive health disparities and minority health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A structured interview survey conducted in the United States found that the median time elapsed from the onset of disordered menses until the diagnosis of POI was two years, reaching five years in a quarter of the women (Alzubaidi et al, 2002). A more recent case series showed that the mean time to diagnose POI from the onset of symptoms was six years (Bhatt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A structured interview survey conducted in the United States found that the median time elapsed from the onset of disordered menses until the diagnosis of POI was two years, reaching five years in a quarter of the women (Alzubaidi et al, 2002). A more recent case series showed that the mean time to diagnose POI from the onset of symptoms was six years (Bhatt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%